CLASSICAL EXPONENTIAL BOUNDS FOR p-GENERALIZED CIRCULAR AND HYPERBOLIC FUNCTIONS - Yogesh J. Bagul; Bharti O. Fande; Ramkrishna M. Dhaigude (Honam mathematical journal, 2025)
In this article, we obtain exponential bounds for the generalized circular and hyperbolic functions with one parameter p. Our results are natural generalizations of some existing results for classical circular and hyperbolic functions.